Factor Structure of Subjective Well-Being of Young Ukrainians - Olefir , Valerii; Bosniuk , Valerii (Insight: the psychological dimensions of society, 2025)
Despite the relatively long history and theoretical and practical significance of studying the subjective well-being of individuals, there is currently no consensus regarding its structure. It was widely recognized that life satisfaction and positive and negative affects are components of subjective well-being; however, the relationship among these components within a single construct remains a subject of debate. The main aim of this study was to investigate the factor structure of subjective well-being by comparing competing theoretical models of the construct’s conceptualization on a sample of Ukrainians (N = 1111 higher education students; age range 18–26 years; 59.0% women, 41.0% men). Methods. Data collection was conducted via the online service Google Forms using Ukrainian versions of the Satisfaction with Life Scale (SWLS) and the Scale of Positive and Negative Experiences (SPANE). To assess the fit of the empirical data to the theoretical models of the structure of subjective well-being, traditional and bifactor confirmatory factor analysis, as well as classic exploratory structural equation modeling and its bifactor variant were applied. The selection of the best model from the competing ones was based on Akaike’s information criterion weights, which consider both the accuracy of the model description and its parsimony. Results. Four models of the factor structure of subjective well-being demonstrated adequate correspondence to the empirical data according to traditional criteria. The correlations between the three latent factors of subjective well-being were moderate and aligned with the expected directions. Akaike information criterion weights indicated that the bifactor model of exploratory structural equation modeling best describes the data from the examined set of candidate models. The consideration of cross-loadings between the items of the questionnaires in this model led to a more accurate representation of the structure of subjective well-being. Measurement invariance across gender was achieved at the configurational, metric, and scalar levels according to this model. Discussion and Conclusions. The bifactor model of exploratory structural equation modeling, featuring a strong general integral factor of subjective well-being and three corresponding subgroups, reliably reflects the three-component structure for both men and women.
Keywords: life satisfaction; positive affect; negative affect; measurement invariance; exploratory structural equation modeling